Age‐ and gender‐related regional variations of human brain cortical thickness, complexity, and gradient in the third decade. Issue 6 (18th October 2013) - Creze, Maud; Versheure, Leslie; Besson, Pierre; Sauvage, Chloe; Leclerc, Xavier; Jissendi‐Tchofo, Patrice
Abstract Brain functional and cytoarchitectural maturation continue until adulthood, but little is known about the evolution of the regional pattern of cortical thickness (CT), complexity (CC), and intensity or gradient (CG) in young adults. We attempted to detect global and regional age‐ and gender‐related variations of brain CT, CC, and CG, in 28 healthy young adults (19–33 years) using a three‐dimensional T1‐weighted magnetic resonance imaging sequence and surface‐based methods. Whole brain interindividual variations of CT and CG were similar to that in the literature. As a new finding, age‐ and gender‐related variations significantly affected brain complexity (P < 0.01) on posterior cingulate and middle temporal cortices (age), and the fronto‐orbital cortex (gender), all in the right hemisphere. Regions of interest analyses showed age and gender significant interaction (P < 0.05) on the temporopolar, inferior, and middle temporal‐entorrhinal cortices bilaterally, as well as left inferior parietal. In addition, we found significant inverse correlations between CT and CC and between CT and CG over the whole brain and markedly in precentral and occipital areas. Our findings differ in details from previous reports and may correlate with late brain maturation and learning plasticity in young adults' brain in the third decade. Hum Brain Mapp 35:2817–2835, 2014. © 2013 Wiley Periodicals, Inc.